Whale Call Data for the North Pacific November 1995 through July 1999 Occurrence of Calling Whales and Source Locations from SOSUS and Other Acoustic Systems - Watkins, William A.; George, Joseph E.; Daher, Mary Ann; Mullin, Kristina; Martin, Darel L. (2000)
Calls of blue whales (Balaenoptera musculus), fin whales (Balaenoptera physalus), and humpback whales (Megaptera novaeangliae) were identified in the data from U.S. Navy Sound Surveillance System (SOSUS) and other hydrophone arrays. These data on calling whales from November 1995 through July 1999 have been listed here for four offshore, deep-water Regions along continental margins of the North and Northeast Pacific. The occurrence of calling whales was monitored during two-day periods each week. Call data recorded from each array identified species, call occurrence, variation, received beam, and relative numbers of calling whales. This allowed assessment of seasonal distribution of calls for the different species, and provided locations for sources received at multiple arrays. Blue whale tonal sounds were distributed widely, received most in the NW Region, with a peak in occurrence in the fall. Fin whale "20-Hz" repetitive pulse sequences were received from whales grouped in local areas in all Regions, with a peak in occurrence in midwinter. Humpback songs were received from December through May particularly in the SE Region. The offshore listening systems allowed basin-wide monitoring of the seasonal distribution of these calling whales.